1998
DOI: 10.1182/blood.v92.7.2495.2495_2495_2502
|View full text |Cite
|
Sign up to set email alerts
|

Mcl-1 Expression in Human Neutrophils: Regulation by Cytokines and Correlation With Cell Survival

Abstract: Human neutrophils possess a very short half-life because they constitutively undergo apoptosis. Cytokines, such as granulocyte-macrophage colony-stimulating factor (GM-CSF), and other agents can rescue neutrophils from apoptosis but the molecular mechanisms involved in this rescue are undefined. Here, we show by Western blotting that human neutrophils do not express Bcl-2 or Bcl-X but constitutively express Bax. However, cellular levels of these proteins are unaffected by agents which either accelerate or dela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
93
1
4

Year Published

1999
1999
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 82 publications
(110 citation statements)
references
References 32 publications
6
93
1
4
Order By: Relevance
“…Spontaneous PMN apoptosis has been shown to be a caspasedependent apoptotic program because PMNs incubated with caspase inhibitors do not undergo apoptosis and can be triggered by extrinsic and intrinsic apoptotic pathways (47). There are several studies that associate spontaneous PMN apoptosis with intrinsic mitochondrial signaling, including a decline in antiapoptotic protein Mcl-1, translocation of proapoptotic Bax to the mitochondrium, and subsequent release of cytochrome c and caspase 9 activation (48,49). Other studies have described caspase 8-dependent spontaneous PMN apoptosis, involving ligand-independent clustering of death receptors (24).…”
Section: Discussionmentioning
confidence: 99%
“…Spontaneous PMN apoptosis has been shown to be a caspasedependent apoptotic program because PMNs incubated with caspase inhibitors do not undergo apoptosis and can be triggered by extrinsic and intrinsic apoptotic pathways (47). There are several studies that associate spontaneous PMN apoptosis with intrinsic mitochondrial signaling, including a decline in antiapoptotic protein Mcl-1, translocation of proapoptotic Bax to the mitochondrium, and subsequent release of cytochrome c and caspase 9 activation (48,49). Other studies have described caspase 8-dependent spontaneous PMN apoptosis, involving ligand-independent clustering of death receptors (24).…”
Section: Discussionmentioning
confidence: 99%
“…It has been demonstrated that an improvement of monocyte survival can be achieved by the addition of pro-inflammatory cytokines such as tumour necrosis factoralpha (TNF-a), IL-1b and GM-CSF (Mangan and Wahl, 1991;Moulding et al, 1998;Flad et al, 1999). In a previous report, we demonstrated that HP-NAP stimulates monocytes to secrete TNF-a (Amedei et al, 2006) but the possibility that also IL-1b and GM-CSF could be induced has not been yet investigated.…”
Section: Il-1b Is Crucial For the Improvement Of Monocytes Survival Imentioning
confidence: 99%
“…It also has a C-terminal hydrophobic domain that is responsible for the localization of Mcl-1 to membranes within the cell, in particular to the mitochondrial membrane (Yang et al, 1996;Akgul et al, 2000). While it appears that Mcl-1 may not be as potent a protector against apoptosis as Bcl-2 (Reynolds et al, 1996), it does appear to be the main anti-apoptotic protein in some cell types including neutrophils (Moulding et al, 1998). Unlike other Bcl-2 family members, Mcl-1 contains a large region consisting of two PEST sequences that have been thought to target Mcl-1 for rapid degradation within the cell.…”
mentioning
confidence: 99%
“…The expression of Mcl-1 can be regulated at a transcriptional as well as a post-translational level. Its expression is increased in response to signalling from a number of different cytokines (Chao et al, 1998;Moulding et al, 1998;Huang et al, 2000;Puthier et al, 2001;Pelletier et al, 2002;Tumang et al, 2002). A recent study shows that Mcl-1 is rapidly degraded by the proteasome during induction of apoptosis by UV irradiation in Hela cells (Nijhawan et al, 2003).…”
mentioning
confidence: 99%